Entrepreneurship in Central Europe after COVID-19: Resilience amid a Crisis - Dvouletý Ondřej (Foresight and STI Governance)
This article aims to provide insights into the development of entrepreneurial activity in selected Central European countries, formerly transition economies, after the global COVID-19 pandemic. The objective of the study is to understand whether and how the pandemic reshaped the structure of entrepreneurship in the Czech Republic, Hungary, Poland, and Slovakia. Data from Eurostat, covering both individual-level activity and structural business statistics, were used to determine the answer three years after the start of the COVID-19 crisis. The results from statistical testing and multivariate regression models provide straightforward answers. In the vast majority of the studied indicators, entrepreneurial activity has even increased compared to the pre-pandemic values, with a few exceptions such as employer entrepreneurship, where the results were not statistically conclusive. From the perspective of structural business statistics, we observe the highest increase in information and communication sectors of the studied economies, which might be associated with the need to shift economic and social activities online. The article demonstrates, using the example of the COVID-19 crisis, that even external shocks can boost the exploitation of new business opportunities and entrepreneurial development. In particular, it is argued that the pandemic has sped up the entrepreneurs’ adoption of digital processes and agendas.